2015
DOI: 10.1186/s10194-015-0503-y
|View full text |Cite
|
Sign up to set email alerts
|

Burden of migraine related to menses: results from the AMPP study

Abstract: BackgroundStudies of the difference between menstrually associated and non-menstrually associated migraine are somewhat controversial. The majority of studies have focused on comparing menstrual to non-menstrual attacks rather than comparing study groups with different migraine diagnoses with respect to menstruation. As there is limited knowledge available on the overall impact and burden of migraine among groups of women with and without menstrually associated migraine our goal was to examine differences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
61
2
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 29 publications
(44 reference statements)
3
61
2
4
Order By: Relevance
“…Just like we have established, the American Migraine Prevalence and Prevention (AMPP) study found that women with MM were more impaired by attacks while women with MAM had overall highest burden, likely due to experiencing migraines on additional days. 24…”
Section: Discussionmentioning
confidence: 99%
“…Just like we have established, the American Migraine Prevalence and Prevention (AMPP) study found that women with MM were more impaired by attacks while women with MAM had overall highest burden, likely due to experiencing migraines on additional days. 24…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 18% of women and 6% of men in the United States are affected by migraine, a neurovascular disorder characterized by recurrent headache attacks involving nausea, photophobia, phonophobia, and exacerbation by physical activity (Stewart et al, ; Bigal et al, ). Migraine is the fourth leading cause of disability in women worldwide, with women migraineurs experiencing significant burden of disease (Hu et al, ; Lipton et al, ; Pavlovic et al, ) compared with men (Buse et al, ). The female preponderance of migraine has been recognized since ancient times (Welch et al, ) and has been supported by multiple areas of research.…”
Section: Introductionmentioning
confidence: 99%
“…Overall, MO and MA sufferers account for ∼70% and 20‐30% of migraineurs, respectively. ICHD‐III also describes other migraine subtypes: chronic migraine is diagnosed in patients who experience frequent or almost continuous migraine symptoms, and is often linked with medication overuse; more than 50% of females suffering from MO report a menstrual association, which has led to the further classification of menstrual migraine; and hemiplegic migraine (HM) is a rare severe form of MA that also features motor weakness.…”
Section: Introductionmentioning
confidence: 99%